Association of JMJD2B and Hypoxia-Inducible Factor 1 Expressions with Poor Prognosis in Osteosarcoma. (31st July 2020) - Liu, Xujian; Zhang, Qianqian; Zhao, Yi; Xun, Jianjun; Wu, Hongzeng; Feng, Helin
Abstract : Background . JMJD2B has been reported to be implicated in malignant tumors. This study is aimed at exploring the expression and prognostic significance of JMJD2B in osteosarcoma and its association with hypoxia-inducible factor 1 (HIF1). Methods . The histopathological and clinical characteristics were retrospectively reviewed from 53 osteosarcoma patients. JMJD2B and HIF1 were examined by immunohistochemical staining of paraffin-embedded osteosarcoma samples, and their association with clinical characteristics was examined by Spearman's test. Overall survival was examined by Kaplan-Meier analysis, and prognostic factors were identified by univariate and multivariate regression analyses. Results . JMJD2B and HIF1 expression levels were both significantly associated with Enneking stage, distant metastasis, and neoadjuvant chemotherapy, and the JMJD2B and HIF1 expressions were positively correlated (p < 0.001, R = 0.752 ). In addition, univariate analysis showed that the expression of both JMJD2B and HIF1 was significantly associated with overall survival, but multivariate analysis showed that only JMJD2B expression was significantly associated with overall survival in osteosarcoma patients. Conclusions . JMJD2B and HIF1 expression levels show significant correlation with osteosarcoma progression, and JMJD2B could predict poor prognosis of osteosarcoma patients.